The Croatian future tense : immediate, directed and non-subjectified - Stanojević, Mateusz-Milan; Geld, Renata (2012)
The future tense in Croatian is formed using the present tense of the auxiliary htjeti ‘want’ (which may be cliticized ; e.g. hoću ‘I will’ > ću, etc.) and the infinitive, as in igra će trajati ‘the game will last’. It may refer to the future (e.g. Sutra ću te nazvati ‘I will call you tomorrow’), general truths (Dok je novca, bit će i prijatelja ‘While there is money, there will be friends’) and has some other minor uses (Silić and Pranjković 2005: 193-194). It has been suggested that the Croatian future tense is epistemically immediate (Author 2011), which is cross-linguistically plausible (cf. e.g. Dahl 2000 ; Langacker 2011). The aim of this paper is to show that the Croatian future tense expresses a non-subjectified future-directed epistemic immediacy. This is in line with mixed tense/aspect view of the Croatian TAM system. There are several pieces of evidence for this. Firstly, the future tense may be used in the protasis of actual hypotheticals much like the present tense (which is epistemically immediate ; cf. Author 2007), but it cannot be used when the ground is shifted to a counterfactual virtuality (cf. (1) and (2)): (1) Ako će ovako igrati, onda će izgubiti. ‘If they play like this, they will lose’ But not: (2) *Da će ovako igrati, onda bi izgubili. The Croatian present tense may be used in both of these – expressing epistemic immediacy with ako ‘if’, (Ako ovako igraju, onda će izgubiti) and a virtual (epistemically immediate) point from a surrogate ground with da ‘if’ (Da ovako igraju onda bi izgubili ‘If they played like this, they would lose’). The future tense is impossible in (2) because the counterfactual context would require a suspension of its future directedness. No such directedness appears in the present tense, which simply refers to immediacy. Secondly, the future tense is not completely grammaticalized in form or meaning. Thus, it has different forms for different persons, and clitics are used alongside full auxiliary forms (unlike, e.g., Bulgarian, with its single clitic šte). Semantically, it has not (completely) developed towards subjectified modal meanings on the future tense grammaticalization cline (Bybee, Perkins and Pagliuca 1991: 26-29), which suggests that it is not extremely subjectified. Thirdly, a corpus study (random sample of 1000 tokens each of the future and the present tense from the Croatian National Corpus) suggests that the future tense is generally used once a “contextual baseline” is established. In most cases, it tends to be introduced by a complementizer (cf. objavljeno da in (3)) or another space builder: (3) Iako je potkraj prošlog tjedna objavljeno da će se … pokušati riješiti pitanje. ‘Although it was announced last week that they will attempt to resolve the issue…’ Moreover, it rarely appears in simple SVO structures (e.g. Borussia će ugostiti Arsenal ‘Borrusia will host Arsenal’). In the present tense, simple SVO structures predominate. Thus, the future tense requires scaffolding connecting it to the ground, and the present tense does not, because of its subjectification. In terms of Cutrer (1994: 89-90), the future space is necessarily viewed from a parent space (which is the viewpoint), whereas the present is not. On a more general scale, this analysis is in line with a mixed tense/aspect-based view of the Croatian TAM system, situating Croatian into the transitional zone among Slavic languages (cf. e.g. Dickey 2000). References Author. 2007. Author. 2011. Cutrer, Michelle. 1994. Time and Tense in Narratives and Everyday Language. Ph. D. dissertation, San Diego: University of California, San Diego. Dahl, Östen. 2000. “The grammar of future time reference in European languages.” In Tense and aspect in the languages of Europe, ed. Östen Dahl, 309–328. Berlin, New York: Mouton de Gruyter. Dickey, Stephen M. 2000. Parameters of Slavic Aspect: A Cognitive Approach. Stanford: Center for the Study of Language and Information. Langacker, Ronald W. 2011. “The English present: Temporal coincidence vs. epistemic immediacy.” In Cognitive Approaches to Tense, Aspect and Epistemic Modality, ed. Frank Brisard and Adele Patard, 45–86. Amsterdam, Philadelphia: John Benjamins. Silić, Josip, and Ivo Pranjković. 2005. Gramatika hrvatskoga jezika za gimnazije i visoka učilišta. Zagreb: Školska knjiga.
Projekt MZOS
ENG